A Global Assessment of the Chemical Recalcitrance of Seagrass Tissues: Implications for Long-Term Carbon Sequestration - Trevathan-Tackett, Stacey M.; Macreadie, Peter I.; Sanderman, Jonathan; Baldock, Jeff; Howes, Johanna M.; Ralph, Peter J. (Frontiers in Plant Science, 2017)
Seagrass ecosystems have recently been identified for their role in climate change mitigation due to their globally-significant carbon sinks; yet, the capacity of seagrasses to sequester carbon has been shown to vary greatly among seagrass ecosystems. The recalcitrant nature of seagrass tissues, or the resistance to degradation back into carbon dioxide, is one aspect thought to influence sediment carbon stocks. In this study, a global survey investigated how the macromolecular chemistry of seagrass leaves, sheaths/stems, rhizomes and roots varied across 23 species from 16 countries. The goal was to understand how this seagrass chemistry might influence the capacity of seagrasses to contribute to sediment carbon stocks. Three non-destructive analytical chemical analyses were used to investigate seagrass chemistry: thermogravimetric analysis and solid state 13C-NMR and infrared spectroscopy. A strong latitudinal influence on carbon quality was found, whereby temperate seagrasses contained 5% relatively more labile carbon, and tropical seagrasses contained 3% relatively more refractory carbon. Sheath/stem tissues significantly varied across taxa, with larger morphologies typically containing more refractory carbon than smaller morphologies. Rhizomes were characterized by a higher proportion of labile carbon (16% of total organic matter compared to 8-10% in other tissues); however, high rhizome biomass production and slower remineralization in anoxic sediments will likely enhance these below-ground tissues’ contributions to long-term carbon stocks. Our study provides a standardized and global dataset on seagrass carbon quality across tissue types, taxa and geography that can be incorporated in carbon sequestration and storage models as well as ecosystem valuation and management strategies.